Probabilistic demand and fragility assessment of welded column splices in steel moment frames. (6th February 2015) - Galasso, Carmine; Stillmaker, Kimberly; Eltit, Christian; Kanvinde, Amit
Summary An assessment of seismic demands and capacities of welded column splice (WCS) connections in steel moment frames is presented. For demand assessment, nonlinear dynamic analyses are conducted for two case‐study buildings, that is, a 4‐story and a 20‐story moment frame. Results from the nonlinear dynamic analyses are assessed through a probabilistic seismic demand analysis (PSDA) framework to characterize recurrence rates of longitudinal flange stress in these connections. The PSDA is applied in two contexts. First, in the context of WCS connections constructed prior to the M 6.7 1994 Northridge earthquake, the PSDA is combined with sophisticated finite element‐based fracture mechanics analysis to compute the mean annual frequencies of fracture in these connections. The pre‐Northridge WCS are especially critical because they feature partial joint penetration and brittle materials that compromise their resistance to fracture. The analysis indicates that the mean annual frequencies of fracture in these connections may be unacceptably high for both the 4‐story and the 20‐story frames. This warrants a serious and urgent consideration of retrofit strategies. These findings are attributed to the brittleness of the pre‐Northridge splices (as indicated by the fracture mechanics simulations), as well as the force‐controlled nature of these components, wherein low‐intensity ground motions contribute disproportionately to fracture risk, as evidenced by fracture risk disaggregation. Second, in the context of new construction, the PSDA provides meaningful stress magnitudes for design. Currently, WCS connections employ complete joint penetration welds with the intent to develop the smaller column flange in yielding. The PSDA conducted in this study suggests that this requirement may be too stringent because stress demands in the splices corresponding even to high return periods (e.g., 2475 years) are significantly lower (~40 ksi), as compared with the stress required to yield the column (~55 ksi). Limitations of the study are outlined. Copyright © 2015 John Wiley & Sons, Ltd.